Ksiega swiat i obyczajow zydowskich : bylo, minelo-- - Siemienski, Mieczyslaw (Warszawa : Wydawn. Interpress, 1993)
A short study of Jewish religious holidays and customs.
Keywords: Judaism -- Customs and practices; Jewish art and symbolism